Characterization and antibacterial properties of soil streptomyces - Tasrip, Nor Asmara (2012)
This study was to examine distribution of aerial mass colors and antibacterial activities of 39 Streptomyces isolates from soil, and potential genetic relation of the phenotypes by Random Amplification of Polymorphic DNA (RAPD) analysis. Streptomyces griseus ATCC 10137 strain was also included as a reference strain (n =40). Identification was done by conventional and molecular approaches (16S rRNA and rpoB genes sequence homology). These sequences were further analyzed by using UPGMA (Unweighted Pair Group Method with Arithmetic Mean) method to build phylogenetic tree for 16S rRNA gene. The phylogenetic tree showed a diverse evolutionary pedigree of the isolates in 6 major clusters. Based on International Streptomycetes Project 2 (ISP-2) media, the aerial mass colors observed were categorized as Yellow (n = 15), Grey (n = 9), Brown (n = 7), White (n = 6) and Others (n = 3). Antibacterial activities were assessed on Muller-Hinton agar (MHA) and Trypticase Soy agar (TSA) by perpendicular streak method against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Salmonella sp. and Enterococcus sp. MHA demonstrated 15 isolates with broad spectrum antibacterial activities and 18 as non-broad spectrum. On the contrary, TSA gave lower proportions with 15 and 9 isolates respectively. A high proportion of isolates with non-White color showed antibacterial activities to suggest a potential correlation. RAPD dendogram (a composite of three random primers) also clustered majority of them but segregated those of White color, which showed less antibacterial activities, in a different cluster. Thus, a correlation between aerial mass color and antibacterial property, with a potential genetic linkage, could be assumed.